PENGARUH KONSERVATISME AKUNTANSI, MANAJEMEN LABA, DAN KETEPATAN PELAPORAN KEUANGAN TERHADAP STRATEGI BISNIS PROSPEKTOR DAN DEFENDER (Studi Empiris pada Perusahaan Sektor Consumer Cyclical yang terdaftar di Bursa Efek Indonesia tahun 2021-2024) - Adzana Rakhmania Putri; R. R. Sri Handayani (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of accounting conservatism, earnings management, and financial reporting timeliness on the business strategies of prospectors and defenders in consumer cyclical companies listed on the Indonesia Stock Exchange for the period 2021–2024. This study is based on the Behavioral Agency Model, which explains that managers' strategic decisions are influenced by their perception of risk and the incentives they face. The research method uses a quantitative approach with multiple linear regression analysis (Ordinary Least Squares). The research sample was obtained through non-probability sampling techniques with a total of 258 company observations. Business strategies are classified into prospectors and defenders based on four strategy proxies. Earnings management is measured using the Modified Jones Model, while the timeliness of financial reporting is measured using audit report lag. This study also used control variables in the form of company size, market-to-book ratio, profitability, leverage, sales growth, and liquidity. The results show that accounting conservatism has a positive effect on companies' tendency to choose a defender business strategy. Conversely, earnings management is not proven to have an effect on the selection of a prospector business strategy. In addition, companies that submit their financial reports more timely tend to choose a defender business strategy. These findings indicate that financial reporting characteristics play a role in influencing companies' business strategy orientation.